PULMONARY EMBOLISM WITH ANTIPHOSPHOLIPID SYNDROME: A CASE REPORT - Purwowiyoto, Sidhi Laksono; M, Ferel; R, Yeria; Halomoan, Reynaldo; Kurniawan (Sanus Medical Journal, 2021)
Antiphospolypid síndrome (APS) is a systemic autoimmune condition that is related to vascular thrombosis. Patients with APS are at risk for developing pulmonary embolism (PE) events. In this case, we present a 68 years old female with complaints of sudden onset of persistent shortness of breath for two days. No past medical history was identified. Physical and diagnostic examination revealed the presence of PE and antiphospolipid antibodies. Diagnosis of PE and APS were made. Patients then received initial anticoagulant using enoxaparin subcutaneously. Initial anticoagulants in patients with APS and PE should be administered. However, it is important to choose the right anticoagulant. DOAC is contraindicated due to the increased risk of thromboembolic events.